2004
DOI: 10.1104/pp.104.040022
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Modulation in the Response of the Primary Root of Arabidopsis to Salt Stress

Abstract: Salt stress inhibits plant growth and development. We investigated the importance of cell cycle regulation in mediating the primary root growth response of Arabidopsis to salt stress. When seedlings were transferred to media with increasing concentrations of NaCl, root growth rate was progressively reduced. At day 3 after transfer of seedlings to growth medium containing 0.5% NaCl the primary roots grew at a constant rate well below that prior to the transfer, whereas those transferred to control medium kept a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
255
4
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(297 citation statements)
references
References 48 publications
35
255
4
3
Order By: Relevance
“…The decline in pod length and circumference as a result of decrease in crop water requirements is in line with work done by West et al (2004) who reported that irrigation increases size and weight of fruit and that of Viets (1998) who found that low utilization of water deficient crops has poor carbohydrate utilization and therefore fruit decrease in size (pod length and circumference).…”
Section: Pod Length: Fromsupporting
confidence: 71%
“…The decline in pod length and circumference as a result of decrease in crop water requirements is in line with work done by West et al (2004) who reported that irrigation increases size and weight of fruit and that of Viets (1998) who found that low utilization of water deficient crops has poor carbohydrate utilization and therefore fruit decrease in size (pod length and circumference).…”
Section: Pod Length: Fromsupporting
confidence: 71%
“…They reported that leaf growth inhibition by low night temperature is tightly linked to the reduction of cell production which is a consequence of prolonged cell cycle duration and not of a reduced cell number in the leaf meristem. West et al (2004) indicated that decrease in cell production and a smaller mature cell length was the reason of growth reduction of the Arabidopsis stressed roots but average cell cycle duration was not affected. Thus, the reduced cell production was a consequence of smaller number of dividing cells (meristem size reduction).…”
Section: Discussionmentioning
confidence: 99%
“…Salinity arrests the cell cycle transiently by reducing the expression and activity of cyclins and cyclin-dependent kinases that results in fewer cells in the meristem, thus limiting growth (10). In Arabidopsis, the reduction in root meristem size and root growth during salt stress is correlated with the downregulation of CDC2a (cyclin-dependent kinase), CycA2;1 and CycB1;1 (mitotic cyclins) (11).…”
Section: Effect Of Salinity On Plant Developmentmentioning
confidence: 99%
“…In Arabidopsis, the reduction in root meristem size and root growth during salt stress is correlated with the downregulation of CDC2a (cyclin-dependent kinase), CycA2;1 and CycB1;1 (mitotic cyclins) (11). The activity of cyclin-dependent kinase is diminished also by post-translational inhibition during salt stress (10). Salt stress-induced abscisic acid (ABA) may also mediate cell cycle regulation.…”
Section: Effect Of Salinity On Plant Developmentmentioning
confidence: 99%